Dynamics -- formulas and problems : engineering mechanics. 3 - Gross, D.; Ehlers, Wolfgang; Wriggers, P.; Schröder, Jörg (Mechanical engineer); Müller, Ralf, Prof. Dr.-Ing (Springer, 2016)
This book contains the most important formulas and more than 190 completely solved problems from Kinetics and Hydrodynamics. It provides engineering students material to improve their skills and helps to gain experience in solving engineering problems. Particular emphasis is placed on finding the solution path and formulating the basic equations. Topics include: - Kinematics of a Point - Kinetics of a Point Mass- Dynamics of a System of Point Masses - Kinematics of Rigid Bodies - Kinetics of Rigid Bodies - Impact - Vibrations - Non-Inertial Reference Frames - Hydrodynamics .